IMPACT OF PEER RELATIONS UPON SELF-ESTEEM OF JUVENILE DELINQUENTS - Khusrhid, Maryam; Rehman, Ghazala (Journal of Pakistan Psychiatric Society, 2006)
Objective: This study aimed at exploring the impact of peer relations on the self-esteem of juvenile delinquents. Design: Cross sectional comparative study. Place and Duration of Study: This study was conducted in various male Juvenile jails of Punjab province, Pakistan during 2003. Subjects and Methods: A sample of 200 male convicted juvenile delinquents, who were taken from the Juvenile jails of Multan (n=70), Bahawalapur (n=70) and Fasialabad (n=60). This study was completed during one year time period. The Juvenile were approached with the permission of jail authorities and only those subjects included (i) who gave their informed consent to participate in the study and (ii) who were present at the time of study. Results: The age range of the sample was between 13-to-18 years (M=16.36, SD=1.49) and they belonged to lower and middle socio-economic class. Their categories of crimes ranged from murder to crimes like shoplifting, dacoits, and theft etc. For the measurement of peer stressors and self-esteem of juveniles, Urdu translation of Hudson’s (1982) Index of Self-esteem (ISE), and Index of Peer Relations (IPR) were used. The reliability estimates of scales showed high internal consistency reliability of the measures for the sample of our study. Results indicated highly significant correlation between the scores of ISE, and IPR. Conclusion: The findings of the study suggest that juveniles having low self-esteem have faced higher stressors in peer relations as compared to those juveniles having high self-esteem, and juveniles belonging to lower socio-economic class have more problems with their self-esteem and face more peer stressors compared to the juveniles belonging from middle socio-economic class. Keywords: Juvenile delinquency, Peer relationship, Self-esteem